High-symmetry approximations of AX3 crystal structures retrieved with the method of hierarchical trees - A. G, Panfilov; S. A., Vaganov (JOURNAL OF ADVANCES IN PHYSICS, 2021)
The hierarchical trees have been constructed for the AX3 crystal family, significant steps of this construction being explained in detail. It has made possible to establish the archetypes of the crystal structures that are high-symmetry approximations for subfamilies of the crystals under consideration.